Impact of Shear Connector Spacing in Composite Construction Incorporating Cold-Formed Steel Channel Lipped Section - Saggaff, Anis; Lawan, Mustapha Muhammad; Tahir, Mahmood Md; Mirza, Jahangir (Review of Industrial Engineering Letters, 2016)
Composite construction with traditional Hot Rolled Steel (HRS) sections has been known to perform much better than with Cold-Formed Steel (CFS) sections for decades; as observed by extensive rules and requirements for their design as prescribed in current design codes. There is, however, limited technical information available about the use of composite systems that incorporates the use of light gauge steel sections, despite the potentials of the system in residential and light industrial constructions. However, the composite action of CFS with an in-situ concrete, especially Self-Compacting Concrete (SCC) using bolted shear connector has not yet established. Therefore, this study attempted to investigate the behaviour of bolted shear connector used with SCC and CFS to form a composite beam system at designated longitudinal spacing. Push-out and full-scale test specimens of longitudinal spacing of 250 mm and 300 mm with bolted shear connector of grade 8.8 installed with single nut and washer on the CFS flange and beneath it were fabricated, cast and tested till failure occurred. The experimental test results shows that the bolted shear connector possessed good ultimate strength and ultimate moment capacities with an increase in the longitudinal spacing of the bolted shear connector from 250 mm and to 300 mm respectively. It was therefore concluded that, longitudinal spacing between bolted shear connectors had significantly influenced the shear connector strength capacities.